2012
DOI: 10.1016/j.resmic.2012.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Offense and defense: microbial membrane vesicles play both ways

Abstract: Microbes have evolved over millennia to become adapted and specialized to the environments that they occupy. These environments may include water or soil, extreme environments such as hydrothermal vents, and can even include a host organism. To become adapted to these locations, microbes have evolved specific tools to mediate interactions with the environment. One such tool that prokaryotes have evolved includes the production of membrane vesicles (MVs). MVs are 10–300 nm spherical blebs derived from the outer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
147
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(151 citation statements)
references
References 123 publications
3
147
0
1
Order By: Relevance
“…Based on these findings, we hypothesized that the P. aeruginosa PA14-derived exoproteome competes with bacterial binding to NETs. Prior studies revealed that P. aeruginosa spontaneously, or under stress, produces OMVs (29). When comparing the recently identified P. aeruginosa PA14 OMV proteome (30) to the NETassociated proteome, 81 proteins were shared (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…Based on these findings, we hypothesized that the P. aeruginosa PA14-derived exoproteome competes with bacterial binding to NETs. Prior studies revealed that P. aeruginosa spontaneously, or under stress, produces OMVs (29). When comparing the recently identified P. aeruginosa PA14 OMV proteome (30) to the NETassociated proteome, 81 proteins were shared (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…OMV cargo proteins are protected against degradation and can be transported over long distances in a concentrated manner (57,60). While OMVs from animal-pathogenic bacteria presumably fuse with the host cell membrane to deliver virulence factors (61), the access of OMVs from plant pathogens to the host cell membrane is presumably hindered by the plant cell wall. To date, OMVs from plant-pathogenic bacteria have only been reported for X. campestris pv.…”
Section: Discussionmentioning
confidence: 99%
“…E xtracellular vesicles are produced by all branches of microbial life (1). Most thoroughly studied in Gram-negative bacteria, the functions of these vesicles ranges from disposal of waste products and misfolded proteins to secretion of quorum-sensing signals to delivery of virulence-associated molecules (2). In the fungal kingdom, extracellular vesicles were first described in Cryptococcus neoformans and have subsequently been discovered in a variety of basidio-and ascomycetes (3)(4)(5).…”
mentioning
confidence: 99%